Using 3DMax Software to Assist in Researching the Application of Installation Art in Exhibition Design. Issue 3 (October 2020) - Lv, Qingxin
Abstract: In the art of installation, the environment is a very important part of it, and then people have changed into the active interpretation form of the content with this passive feeling of appearance and separation. Any type of art form, when mobilizing the human senses, is a special way of human understanding and communication, but it also includes the accepted information sensory system, the processing of the information system, and other thinking activities in the installation art. In addition, the display design generally involves a mobile space, at this time, as the main body of the whole display activity, the specific space formed by this display forms a high degree of interaction with the display activity. If the design of the exhibition space is reasonable and the theme of the space is very clear, then on this basis, this kind of exhibition space is very good and can be regarded as a perfect plastic art. 3DMAX technology can make the installation art more three-dimensional and clear. Therefore, the author discussed the use of 3DMax software to assist in the design and display of installation art.